Efeito do tratamento de superfície na resistência de união à microtração de cimentos resinosos à cerâmica In Ceram Alumina - Peixoto, Letícia Monteiro (2009)
The aim of this in Vitro study was to evaluate the microtensile bond strength and the fracture mode of In Ceram Alumina (Vita Zahnfabrik) subjected to resin bonding with different surface treatments. Twenty blocks of ceramic In Ceram Alumina and resin composite Filtek Z350 (3M/ESPE) were made with dimensions of 7mm x 7mm x 5mm. The ceramic blocks were divided into four groups according to the surface treatment and cement used: grupo 1) Al2O3 sandblasting and bonding with Rely X ARC (3M ESPE), grupo 2) Rocatec System sandblasting (3M ESPE) and bonding with Rely X ARC, grupo 3) Al2O3 sandblasting and bonding with Panavia F (Kuraray), grupo 4) Rocatec System sandblasting and bonding with Panavia F. The samples resin/cement/ceramic were sectioned in a cutting machine Labcut 1010 to obtain sticks with a cross-sectional area of ± 1mm2 They were stored in distilled water (7days/370C) and the microtensile bond strength was recorded in a universal testing machine Emic at a crosshead speed of 0.5mm/min. The failure types were noted in a scanning electron microscopy. The results (MPa) were submitted to ANOVA and Tukey’s test (p<0.05): grupo 1-15,71, grupo 2-24,64, grupo 3- 21,86, grupo 4- 28,19. There was no statistical difference between group 2 and group 3. All failures were mixed. It was concluded that the tribochemical system increase the bond strength between resin cements (Panavia F and Rely X ARC) and In Ceram.